A Review on Adverse Effect of Organochlorinated Pesticides on Reproductive System: Understanding the Impacts of Organochlorinated Pesticides on Reproductive Health (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A pesticide is a substance or mixture of substances intended for preventing, destroying, repelling, or lessening the damage of any pest benefiting the production and yield of agricultural sector and Organ chlorinated pesticides (also known as chlorinated hydrocarbons) are organic compounds attached with five or more chlorine atoms. Most of them were widely used as insecticides for the control of a wide range of insects, and they have a long term residual effect in the environment that effect reproductive system of both male and female. In females it results in alterations in the ovary, ovarian cycle irregularities, impaired fertility, modulation of hormone concentration. In males Reproductive abnormalities, including feminization of males, decreased sperm production, reduced testicular size, infertility, and birth defects have been reported in laboratory animals and wildlife exposed to endocrine-disrupting chemical So, present review emphasizes organ chlorinated pesticides induced toxicity in reproductive system of male and female.